Sense of Place Destinasi Wisata Urban: Kasus Titik Nol Kilometer, Yogyakarta - Bonifasia Yuniar Rifani (Jurnal Kawistara, 2021)
Urban tourism phenomenon has rarely been studied using both tourism and urban studies approach, whereas urban environment play an essential role in tourism attractiveness. This research investigates the considerably high tourist visit in public space of Titik Nol Kilometer Yogyakarta as an urban tourism phonemenon using a multidimensional concept of sense of place which explains relationship between the tourist (people) and the public area (place). The analysis is focused on the place making components that creates sense of place. The sense of place concept is explored through qualitative analysis, with data collected from physical and behavioural mapping, and online interviews with tourists. Overlay and interactive analytical model is performed to identify the sense of place and its component. Sense of place in Titik Nol Kilometer is identified as emotional relationship between tourist and public space setting which becomes not only a place for recreational or creative events performed by the citizen or local people, but also an attractive destination for tourist that brings personal experience of the unique life of Yogyakarta city. Sense of place is created by the connectedness of various elements based on physical setting, activity, and meaning parameters which coherently combined and complement each other’s existence. The process involved the collaboration of planned place making and organic place making, which enable the coexistence of ‘old and new’, and ‘local and tourist’ contrast.